Bovine milk usage and feeding practices for infants in India - Meha Mayuri; Vivek Garg; Chandan Mukherji; Divya Aggarwal; Sanjeev Ganguly (Wolters Kluwer Medknow Publications, 2012)
Background: Milk and dairy products from animal sources (cow's milk or buffalo's milk) are an important part of Indian diet and its consumption starts at an early age. Objective: The purpose of this study is to understand the processing, storage and modifications carried out before bovine milk is fed to the infants and compare it with recommendations by Health Care Professionals (HCPs). Materials and Methods: The study involved assessments involving HCPs and mothers of children below 1 year of age through both qualitative and quantitative methods. Feeding recommendations by HCPs were assessed through a quantitative method. Results: The children are commonly initiated on bovine milk post 3 months of age. The milk is not covered while boiling in 70% cases and boiled at suboptimal temperature (moderate: 62% or low: 31%). Half of the families store milk outside refrigerators openly in the kitchen or rooms. The milk is modified in the majority of cases (81%) before being fed. Modification of the milk was often done with sugar (85%), followed by water (49%), biscuits, fennel seeds, cardamom or infant cereals before feeding the baby. Addition of water was more prevalent among mothers of infants between 3 and 6 months. HCPs do not advise consumption of bovine milk by infants unless there is no other option available. Conclusion: A clear gap exists between recommended and actual practices for infant feeding in India. There is a huge opportunity to educate mothers on importance of breast feeding and benefits of implementing appropriate processing, storage, and consumption practices of bovine milk.